2017
DOI: 10.1007/s00222-017-0746-0
|View full text |Cite
|
Sign up to set email alerts
|

Equiangular lines and spherical codes in Euclidean space

Abstract: A family of lines through the origin in Euclidean space is called equiangular if any pair of lines defines the same angle. The problem of estimating the maximum cardinality of such a family in R n was extensively studied for the last 70 years. Motivated by a question of Lemmens and Seidel from 1973, in this paper we prove that for every fixed angle θ and sufficiently large n there are at most 2n − 2 lines in R n with common angle θ. Moreover, this bound is achieved if and only if θ = arccos . Indeed, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(99 citation statements)
references
References 21 publications
4
79
0
1
Order By: Relevance
“…One can also consider the related problem of, for fixed α ∈ (0, 1), finding N α (d), the maximum number of lines in R d through the origin with pairwise angle arccos α. Motivated by a conjecture of Bukh [4], the asymptotic behaviour of N α (d) was recently shown to be linear in d [3,20].In Table 1 below, we give the currently known (including the improvements from this paper) values or lower and upper bounds for N (d) for d at most 23.…”
mentioning
confidence: 99%
“…One can also consider the related problem of, for fixed α ∈ (0, 1), finding N α (d), the maximum number of lines in R d through the origin with pairwise angle arccos α. Motivated by a conjecture of Bukh [4], the asymptotic behaviour of N α (d) was recently shown to be linear in d [3,20].In Table 1 below, we give the currently known (including the improvements from this paper) values or lower and upper bounds for N (d) for d at most 23.…”
mentioning
confidence: 99%
“…Seidel matrices were introduced by Van Lint and Seidel [62] and studied by many people due to their interesting properties and connections to equiangular lines, two-graphs, strongly regular graphs, mutually unbiased bases and so on (see [10,Section 10.6] and [4,45,73] for example). The connection between Seidel matrices and equiangular lines is perhaps best summarized in [10, p.161]:…”
Section: Seidel Matricesmentioning
confidence: 99%
“…[60,Theorem 3.4]) proved that if N α (d) ≥ 2d, then 1/α is an odd integer. Bukh [12] proved that N α (d) ≤ c α d, where c α is a constant depending only on α. Balla, Dräxler, Keevash and Sudakov [4] improved this bound and showed that for d sufficiently large and α = 1/3, When 1/α is not a totally real algebraic integer, then N α (d) = d. Jiang and Polyanskii [56] studied the set T = {α | α ∈ (0, 1), lim sup d→∞ N α (d)/d > 1} and showed that the closure of T contains the closed interval [0, 1/ √ 5 + 2] using results of Shearer [75] on the spectral radius of unsigned graphs.…”
Section: Seidel Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…A Seidel switching with respect to U transforms G to a graph H by deleting the edges between U and W and adding an edge between vertices u ∈ U and w ∈ W if (u, w) / ∈ E(G). For more details on Seidel matrices and related topics, see [15,11,12,1] and the references there. Seidel switching is an equivalence relation and we say that G and H are switching equivalent.…”
Section: Introductionmentioning
confidence: 99%